Robust and persistent B-cell responses following SARS-CoV-2 vaccine determine protection from SARS-CoV-2 infection - Byrne, Joanne; Gu, Lili; Garcia-Leon, Alejandro; Gaillard, Colette Marie; Saini, Gurvin; Alalwan, Dana; Tomás-Cortázar, Julen; Kenny, Grace; Donohue, Sean; Reynolds, Bearach; O’Gorman, Tessa; Landay, Alan; et al. (Frontiers in Immunology, 2024)
Introduction: A clear immune correlate of protection from SARS-CoV-2 infection has not been defined. We explored antibody, B cell and T cell responses to third-dose vaccine and relationship to incident SARS-CoV-2 infection. Methods: Adults in a prospective cohort provided blood samples at day 0, day 14 and 10 months post third-dose SARS-CoV-2 vaccine. Participants self-reported incident SARS-CoV-2 infection. Plasma anti-SARS-CoV-2 receptor binding domain (RBD) and spike-subunit-1 and spike-subunit-2 antibodies were measured. A sub-study assessed SARS-CoV-2-specific plasma and memory B cell and memory T cell responses in peripheral blood mononuclear cells by ELISpot. Comparative analysis between participants who developed incident infection and uninfected participants utilised non-parametric t-tests, Kaplan-Meier survival analysis and Cox proportional hazard ratios. Results: Of 132 participants, 47(36%) reported incident SARS-CoV-2 infection at a median 16.5(16.25-21) weeks post third-dose vaccination. RBD titres, B cell responses, but not T cell responses, increased post third-dose vaccine. While no significant difference in day 14 antibody titres or T cell responses was observed between participants with and without incident SARS-CoV-2 infection, RBD memory B cell frequencies were significantly higher in those who did not develop infection (10.0%(4.5-16.0%) versus 4.9%(1.6-9.3%), p=0.01). RBD titres and memory B cell frequencies remained significantly higher at 10 months than day 0 levels (p<0.01). Discussion: Robust antibody and B cell responses persisted at 10 months following third-dose vaccination. Higher memory B cell frequencies, rather than antibody titres or T cell responses, predicted protection from subsequent infection, identifying memory B cells as a correlate of protection.